Persepsi pelajar terhadap peranan mentor di dalam pencapaian akademik - Amizah, Bukhari. (Universiti Malaysia Sarawak (UNIMAS), 2003)
The main objective ofthe study is to identify the role ofmentor in academic achievement ofstudents based on students' perception. It also detennines the relationship between role ofmentor as a facilitator, friend, counselor and coach from CGPA aspect, skill in doing assignment and study skills. About 50 respondents were chosen for data collection by using a set questionnaire. Data was analyzed by using SPSS Windows n.o. The findings showed that there are significant relationships between role ofmentor with academic achievement and that mean null hypothesis one until null hypothesis four (Ho 1 -Ho 4) are not accepted. It shows that the roles ofmentor are important to help stlldent achievement. Otherwise, for demographic factor, there are no significant differences between gender and ethnic with academic achievement. Because ofthat null hypothesis five (Ho 5) are accepted. From the findings, the researcher recommends that faculty should emphasize on the role ofmentor because the findings ofthe effect ofthis stlldy show that mentors did not satisfactory play their role asfacilitator, friends, counselors, and coach's.